2009
DOI: 10.1590/s0100-55022009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depressive symptoms in a sample of Brazilian medical students

Abstract: OBJECTIVES: 1 - Verify the prevalence of depressive symptoms in first to fourth-year medical students using the Beck Depression Inventory (BDI). 2 - Establish correlations between target factors and higher or lower BDI scores. 3 - Investigate the relationship between the prevalence of depressive symptoms and the demand for psychological care offered by the Centro Universitário Lusíada. METHOD: Cross-sectional study of 290 first to fourth-year medical students; implementation of the BDI, socio-demographic surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
1
0
5
Order By: Relevance
“…In southern Brazil, the estimated prevalence of depression in the general population of the same age group of that in this study is 12.6% 11 . The present study showed a prevalence of 32.8%, which is similar to that found in other studies that have used the BDI for the analysis of depression among medical students 3,[12][13][14][15] . The observed prevalence rate was higher than that found in two studies that, while using the same cut-off points, reported prevalence rates of depression of 23.1% 12 and 26.8% 13 among medical students.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In southern Brazil, the estimated prevalence of depression in the general population of the same age group of that in this study is 12.6% 11 . The present study showed a prevalence of 32.8%, which is similar to that found in other studies that have used the BDI for the analysis of depression among medical students 3,[12][13][14][15] . The observed prevalence rate was higher than that found in two studies that, while using the same cut-off points, reported prevalence rates of depression of 23.1% 12 and 26.8% 13 among medical students.…”
Section: Discussionsupporting
confidence: 90%
“…During that period, medical students undergo psychological transformations, are still immature and feel insecure about their responsibilities as future physicians 3 . However, similarly to what had occurred in the two mentioned studies, 2,12 there was no statistical significance between the medical school semester and psychiatric disorders in this study.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Teses, dissertações e monografias também foram excluídas da amostra, uma vez que estes trabalhos acadêmicos não passaram pelo processo de validação por pares em periódicos científicos. A análise dos estudos selecionados 6,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] ratificou o encontrado nas revisões de literatura científica quanto à prevalência de sintomas depressivos entre os estudantes de medicina. [1][2][3]5 Contudo, foi encontrada uma variação muito grande entre os resultados do estudo: a prevalência variou de 5,6% a 79%.…”
Section: C) Critérios De Exclusãounclassified
“…Sabe-se que as consequências para os estudantes quando insatisfeitos e frustrados, segundo estudos, é a maior susceptibilidade a problemas acadêmicos e pessoais como sintomas depressivos, desonestidade acadêmica, menor cuidado com a saúde pessoal, alterações nos relacionamentos 5,28 . Aqueles que enfrentam maiores dificuldades com o curso e pior performance acadêmica, tendem a abandoná-lo, segundo revisão sistemática que avaliou as causas de desistências no curso de medicina 29 .…”
Section: Medicinaunclassified